Role of individual and combined inocula on the development of pea root rot - S.K. SUGHA, VINAY SAGAR and (Indian Phytopathology, 2002)
Four pathogens namely Fusarium oxysporum f.sp. pisi, F. solani f.sp. pisi, Rhizoctonia solani and Phoma medicaginis var. pinodella were associated with pea root rot in Himachal Pradesh, India. The role of individual and combined inocula of these pathogens was investigated. F. s. f.sp. pisi had the best competitive ability over other pathogens. Pea seedlings pre-inoculated with P. m. var. pinodella followed by F. s. f.sp. pisi exhibited a significant additive effect on the disease. Mixed inocula of F. o. f.sp pisi with P. m. var. pinodella had a significant suppressive effect and that of R. solani with P. m. var. pinodella an additive effect on the development of pea root-rot disease.